2018
DOI: 10.2106/jbjs.18.00213
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Evaluation of a Custom Energy-Storing Carbon Fiber Orthosis for Patients with Residual Disability After Lower-Limb Trauma

Abstract: Background: The Intrepid Dynamic Exoskeletal Orthosis (IDEO) is a custom energy-storing carbon fiber ankle-foot orthosis developed for lower-extremity trauma patients. Studies conducted at the military treatment facility where the IDEO was developed demonstrated benefits of the IDEO when used with the Return to Run Physical Therapy (RTR PT) program. The current study was designed to determine if results could be replicated at other military treatment facilities and to examine whether early performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…One of the studies did not report the outcome on this test [22]. Another study demonstrated improvement on the IAT with median scores of 29.0 s at the start and 22.5 s after a 4-week training program [23]. This is similar to our results with an IAT improvement with a median score from 30.3 to 22.9 s. Moreover, it is also important to note the reduction in the IQR in this before-and-after design.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies did not report the outcome on this test [22]. Another study demonstrated improvement on the IAT with median scores of 29.0 s at the start and 22.5 s after a 4-week training program [23]. This is similar to our results with an IAT improvement with a median score from 30.3 to 22.9 s. Moreover, it is also important to note the reduction in the IQR in this before-and-after design.…”
Section: Discussionmentioning
confidence: 99%
“…Of the "Independence" papers (N=21 (55%)), 17 ((45%) fit into the "Mobility" subdomain while four (10%) focused on "Activities of Daily Living" 24,30,31,34,35,39,[42][43][44]46,[49][50][51][52][53][54][55][56][57][58] . Of the Social Relations studies (N=6 (16%)), four focused on the "Social Support" subdomain while two (5%) focused on "Personal Relationships" 33,34,41,59,60 .…”
Section: Health Related Quality Of Life Outcomesmentioning
confidence: 99%
“…Although research in this area is solely focused on adults, early anecdotal clinical experience indicates that it may be promising for pediatrics. 27…”
Section: Modern Pediatric Designsmentioning
confidence: 99%